Development and application of crude sap-based recombinase polymerase amplification assay for the detection and occurrence of grapevine geminivirus A in Indian grapevine cultivars - Kishan, Gopi; Kumar, Rakesh; Sharma, Susheel Kumar; Srivastava, Nishant; Gupta, Nitika; Kumar, Ashwini; Baranwal, Virendra Kumar (Frontiers in Plant Science, 2023)
Geminiviruses are known to infect several fields and horticultural crops around the globe. Grapevine geminivirus A (GGVA) was reported in the United States in 2017, and since then, it has been reported in several countries. The complete genome recovered through high-throughput sequencing (HTS)-based virome analysis in Indian grapevine cultivars had all of the six open reading frames (ORFs) and a conserved nonanucleotide sequence 5′-TAATATTAC-3′ similar to all other geminiviruses. Recombinase polymerase amplification (RPA), an isothermal amplification technique, was developed for the detection of GGVA in grapevine samples employing crude sap lysed in 0.5 M NaOH solution and compared with purified DNA/cDNA as a template. One of the key advantages of this assay is that it does not require any purification or isolation of the viral DNA and can be performed in a wide range of temperatures (18°C–46°C) and periods (10–40 min), which makes it a rapid and cost-effective method for the detection of GGVA in grapevine. The developed assay has a sensitivity up to 0.1 fg μl-1 using crude plant sap as a template and detected GGVA in several grapevine cultivars of a major grapevine-growing area. Because of its simplicity and rapidity, it can be replicated for other DNA viruses infecting grapevine and will be a very useful technique for certification and surveillance in different grapevine-growing regions of the country.